{2-Morpholino-N-[1-(2-pyrid-yl)ethyl-idene]ethanamine-κN,N',N''}bis-(thio-cyanato-κN)copper(II) - Gwaram, Nura Suleiman; Ikmal Hisham, Nurul Azimah; Khaledi, Hamid; Ali, Hapipah Mohd (International Union of Crystallography, 2010)
In the title compound, [Cu(NCS)(2)(C(13)H(19)N(3)O)], the Cu(II) ion is five-coordinated by the N,N',N''-tridentate Schiff base and the N atoms of two isothio-cyanate ligands in a square-pyramidal geometry. In the crystal, C-H⋯N, C-H⋯O and C-H⋯S inter-actions link adjacent mol-ecules into layers parallel to the ac plane. A weak inter-molecular π-π inter-action occurs between the aromatic rings with a centroid-centroid distance of 3.9412 (9) Å.